Razlike v občutenju strahu pred kriminalom na javnih prostorih glede na spol - Erkan, Nilgün Çolpan (Urbani izziv, 2021)
Safety is an important issue in large cities. Fear of crime, on the other hand, is an issue independent of actual crime rates, but it is directly related to spatial qualities, affecting people’s feelings of safety. Fear of crime also varies by gender. This study investigates fear of crime in public places in a particularly safe location of a large metropolis. In this context, it focuses on the effects of spatial characteristics on fear of crime and the differences between genders. The study was carried out in one of the safest districts of Istanbul, which women consider safe. In a 2017 survey, 387 male and female participants of varying ages were questioned regarding their fear, when they experienced such fear, and their reasons for fear in public space. According to the results, women felt a certain amount of fear of crime even in a safe district of the city. In addition, gender-based differences concerning fear in public places and the conditions in which fear is felt are significant.
Keywords: fear of crime; gender; Istanbul; javni prostor; ocena tveganja; psihologija spolov; public space; risk assessment; strah pred kriminalom